Le pouvoir disciplinaire chez Calvin - García-Alonso, Marta (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2010)
This paper discusses the doctrinal foundations of criminal law in Calvin’s ecclesiology, namely his theology of the original sin, and its practical implementation in Geneva’s consistory. On these grounds, I analyse the distinction between civil and ecclesiastical criminal law. Both State and Church were granted by Calvin a ius gladii, but only the former can claim a right to impose physical punishment, whereas the latter should just punish spiritually. Here lays, in my view, the difference between law and discipline.